Fault location in loop distribution network using SVM technology. (February 2015) - Deng, Xiangtian; Yuan, Rongxiang; Xiao, Zhenfeng; Li, Timing; Wang, Kaiwen Li Liu
Highlights: The method aims at single-phase grounding fault in distribution loop network. The first step of the method is obtaining fault section. Feature extraction is achieved using Discrete Wavelet Transform. SVM technology is utilized for precise fault point location. The simulations indicate high efficiency and robustness of the proposed method. Abstract: The purpose of this paper is to provide a hierarchical and active fault location method in neutral point non-effectively grounded loop distribution network. It analyzes the distribution of loop closing zero-sequence current with single-phase grounding (SPG) fault occurring in two different topologies. According to the variations characteristics of steady loop closing zero-sequence current, fault section can be determined. Then precise SPG fault position can be got using Discrete Wavelet Transform (DWT) and Support Vector Machine (SVM) technology. Even if the fault point cant be located at the first time, the method can still work by repeating the process till the accurate fault position is located. More than 115, 200 study cases are simulated on the simulation platform built on PSCAD/EMTP. The results indicate that the proposed fault location method is effective and robust for neutral point non-effectively grounded loop distribution network.